Evaluation of groundwater hydrogeochemical characteristics and delineation of geothermal potentialities using multi criteria decision analysis: Case of Tozeur region, Tunisia. (February 2020) - Brahim, Fatma Ben; Boughariou, Emna; Makni, Jalila; Bouri, Salem
Abstract: The use of geothermal energy in Tunisia is limited to its instant use because of the low enthalpy resources, especially in the southern part of the country. The Djerid Basin has remarkable geothermal resources with low to moderate temperatures that have been used only for irrigation of oases and heating greenhouses. In order to evaluate the geothermal potential of groundwater resources of Tozeur region located in the Djerid Basin, a synthetic approach including geological, geophysical, physicochemical, hydrogeological and geothermometric characteristics of groundwater is indispensable. It aims to determine: (1) the evolution of the water chemistry, (2) the origin of thermal waters and their reservoir temperature, (3) the mixing mechanism of geothermal fluid and (4) the mapping of geothermal potentialities with Multi-Criteria-Decision-Analysis (MCDA) using GIS platform. The hydrogeochemical approach revealed that the studied geothermal system is characterized by temperature values ranging between 25 and 75°C and total dissolved solids (TDS) values between 0.7 and 5.8 g/l. Furthermore, the use of silica geothermometers and saturation indices for different solid phases gave estimated geothermal reservoir temperature ranging between 92 and 104 °C and between 100 and 125 °C, respectively. In addition, the equilibrium processes elucidated that the thermal waters are mostly in the oversaturated condition with respect to calcite, aragonite and dolomite, but they are saturated with evaporate minerals. According to the obtained results of the MCDA, the spatial assessment of the potential geothermal areas using Weighted overlay and Boolean logic Models are 37 % and 5 % respectively. The findings in this study contribute to a better understanding of groundwater sustainability for supporting geothermal project on renewable energy and can be used as a synthetic document for realistic management of groundwater resources. Highlights: The traditional geothermal approach could not be accurately applied in a suitability analysis for geothermal resource exploration. GIS Based MCDA Method provides a powerful tool to identify the geothermal potential areas. The geothermal potential map is a suitable tool for supporting thermal groundwater resource management.